2014
DOI: 10.1016/j.mgene.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bovine gene LIPE and possible influence on fatty acid composition of meat

Abstract: LIPE is an intracellular neutral lipase, which is capable of hydrolyzing a variety of esters and plays a key role in the mobilization of fatty acids from diacylglycerols. The objectives of this study were to characterize the genetic polymorphism of bovine LIPE gene and to evaluate the possible association between three SNPs in the coding regions of this gene with the fatty acid composition of meat in a cattle population. Forty-three unrelated animals from different cattle breeds were re-sequenced and 21 SNPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The high level of variability observed in FABP4 was similar to that detected by our group in the bovine LIPE gene (21), which encodes an enzyme that interacts with FABP4 in lipid hydrolysis, using the same sample panel. Currently, the SNPdb has more than 95 million polymorphisms for B. taurus, but two thirds of them are yet to be validated and only 11189 show frequency data.…”
Section: Discussionsupporting
confidence: 84%
“…The high level of variability observed in FABP4 was similar to that detected by our group in the bovine LIPE gene (21), which encodes an enzyme that interacts with FABP4 in lipid hydrolysis, using the same sample panel. Currently, the SNPdb has more than 95 million polymorphisms for B. taurus, but two thirds of them are yet to be validated and only 11189 show frequency data.…”
Section: Discussionsupporting
confidence: 84%
“…The g.78944G>A and g.81959G>A variants in exon 2 led to amino acid changes from glycine to arginine and from serine to asparagine, respectively. Therefore, variations in the amino acid coding region may cause alterations in the HSL protein structures that result in functional HSL lipid metabolism, thereby influencing the meat composition and altering the meat quality traits [38,39]. In the current study, individuals with the AA genotype had lower WBSF values than those with the GG phenotype, possibly because these amino acid mutation variants alter the function of the yak HSL proteins.…”
Section: Discussionmentioning
confidence: 60%
“…Nowadays, an increasing number of observations have demonstrated that the HSL gene is an outstanding candidate for the meat quality traits [22]. This gene encodes for an intracellular neutral lipase that hydrolyzes various estrogens and is involved in mobilizing free fatty acids in living bodies; therefore, changes in the sequence of this gene may alter the fatty acid composition of tissues [38]. The present study is the first to reveal the relationship between the variation in the HSL gene and meat and carcass traits in yaks.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, two SNPs (c.276C>T and c.51C>T) have been found to be associated with carcass and meat quality traits in Chinese Simmental-cross steers [10]. Furthermore, three SNPs (rs109759779, rs109598915, and rs41887406), selected on the basis of evolutionary conservation, were studied and the obtained results suggested a possible association of SNP1 with the levels of oleic acid and total monounsaturated fatty acids (SFA) (p˂0.01), and SNP2 and SNP3 with the level of heneicosylic acid (p˂0.01) [11].…”
Section: Tables-3mentioning
confidence: 99%